Avaliação de motores de tratores agrícolas utilizando dinamômetro móvel - Farias, Marcelo Silveira de (2014)
Tractors are the most used agricultural machines in most mechanized operations in a rural property. This has raised agricultural tractors production and trading. Together with such production raise, questions have also been raised in relation to technical information accuracy provided by manufacturers. In this sense, the performance of an agricultural tractor engine can be known through dynamometric trials, which enable a fast diagnosis of the engine work, as well as the identification of its basic characteristics. This way, the main objective of this work was to compare torque and effective power values of new agricultural tractors engines, from trials realized in portable dynamometer bench with technical information provided by manufacturers. Concerning torque, effective power values and noise emitted by the engine, the objective is specifically to compare different makes and models of new agricultural tractors traded through the program Mais Alimentos; compare tractor motors with the same gross power; evaluate the addition of turbocharger in a agricultural engine; evaluate the sound-level emitted by agricultural engines during dynamometric trials and compare it to the maximum levels established by the Ministry of Labour and Employment regulating norm NR 15. For that, it is used an EGGERS portable eddy current dynamometer, model PT 301 MES. As conclusion, it was verified that Class IV agricultural tractors engines effective power is bigger in comparison to the values provided by manufacturers. As for Class III tractor engines, torque values assessed were bigger when compared to the manufacturers values, while Class V motors presented smaller values.